Globalizacja, regionalizacja, integracja - oddziaływania i reperkusje - Rzeszotarska, Grażyna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
The term - globalization - has multiple meanings. It is a process to be most distinctively observed in economy, inclusive of some complex, dynamic and multidimensional changes that take place within the functioning of human civilization. The roots of globalization may be looked upon as three fundamental issues: advance in technology, techno-economic paradigm, and finally, new civilization structure. Globalization is inevitable but its impact and consequences can be shaped. Thus much can be gained but also much can be lost. This is why some people view it as a beneficial phenomenon whereas others fiercely oppose. Facing the necessity of adaptation processes, one must think over the essence of regional integration together with its significant role in changing the global conditions. The new integration appears as a trend towards concentration and taking efforts to gain political and economic efficiency, in order to adequately prepare for competition and protection of social values. It is also attempting to inflict certain chains of principles, so that proper balance between the means and the aims remained restored. The trends towards regional integration and creating regular integration organizations are characteristic for many parts of the world. They involve the countries which represent different levels of development, different traditions, or even different political forms of government. Both hopes and doubts accompany the process of regional integration. They refer to the influence regional integration will have on future position of the whole group and also of single countries, in terms of economy and politics. A question may be asked: whether the European Union can take the leading part in the process of the so-called "new globalization". It has become a helping tool for other member countries for building external relations, as well as for controlling external influences, at the same time. The issue discussed above, being vital for the European countries, is definitely worth of notice and due studies. Possible scenarios of the development of European integration need to be created. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1191, s. 577-587